Podvertising: Podcast Listeners’ Advertising Attitudes, Consumer Actions and Preference for Host-Read Ads - Moe, Margaret (Journal of Economics and Behavioral Studies, 2023)
While comparatively few scholarly studies exist on podcast advertising, market research substantiates the effectiveness of podcast advertisements. This academic study probed podcast listeners’ attitudes toward podcast advertising and motivations for consumer actions through survey research with 1714 respondents. Extending past research on attitudes toward advertising within a medium (Aam), consumer action, and listener preference for host-read podcast advertisements, this study proposes a theoretical framework that seeks to contribute to a fundamental understanding of how listeners interact with and process podcast advertising. Scale development included modifying existing scales for other media as well as original scale development using qualitative methods that were tested for validity and internal consistency. Results from the survey revealed that: (1) Podcast listeners have favorable attitudes toward podcast advertising, particularly host-read advertisements; (2) Podcast listeners are motivated by functional and socio-emotional reasons for consumer actions, which correlate with positive attitudes toward podcast advertising; and (3) The podcast consumption levels of listeners are moderate predictors of their attitudes toward podcast advertising and subsequent consumer action, while gender and age are weaker predictors.